The characteristics of overweight and obese COVID-19 inpatients at Kebayoran Lama regional public hospital - Vanessa Aryani Octavia Mardani (Indonesian Nutrition Association, 2022)
Coronavirus disease-2019/COVID-19 pandemic had affected globally. The growing prevalence of overweight and obesity globally have risen the concern on its additional impact to worsen this pandemic. Overweight and obesity have previously been shown to increase mortality and severity in patients with COVID-19. Based on those findings, we conducted a study at Kebayoran Lama Regional Public Hospital to provide real database regarding the characteristics of overweight and obese COVID-19 inpatients.